2019
DOI: 10.1097/qai.0000000000001876
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Subjective Improvement of Cognition After Discontinuing Efavirenz in Asymptomatic Patients: A Randomized Controlled Trial

Abstract: Background: Efavirenz is well known for its clinical cognitive side effects. Even asymptomatic patients who switch for other reasons than neurocognitive complaints have reported a subjective improvement in cognitive functioning after discontinuing efavirenz. The aim of this study was to assess the effect on cognition of switching Atripla (TDF/FTC/EFV) to Eviplera (TDF/FTC/RPV), hypothesizing an improvement when discontinuing efavirenz. Setting: A random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Other cART optimisation strategies include a switch from regimes that have been associated with poor neurocognitive performance, particularly efavirenz. Neuropsychological symptoms, and in some cases objective neuropsychological dysfunction, have been noted as side effects of using efavirenz in cART regimes [15], and switching from efavirenz-containing regimes has been associated with improved well-being but not always cognitive benefit in formal testing [37].…”
Section: 'Medical Maximisation' Strategies With Cartmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cART optimisation strategies include a switch from regimes that have been associated with poor neurocognitive performance, particularly efavirenz. Neuropsychological symptoms, and in some cases objective neuropsychological dysfunction, have been noted as side effects of using efavirenz in cART regimes [15], and switching from efavirenz-containing regimes has been associated with improved well-being but not always cognitive benefit in formal testing [37].…”
Section: 'Medical Maximisation' Strategies With Cartmentioning
confidence: 99%
“…Poorly controlled cardiovascular risk factors such as diabetes or hypertension are associated with poorer cognitive outcomes in PLWH [36][37][38][39]. Studies in improved management of those diseases have shown mixed results in improving cognition [42].…”
Section: 'Medical Maximisation' Strategies-management Of Co-morbiditiesmentioning
confidence: 99%
“…This study is a sub-analysis of the ESCAPE trial (Effect of SwitChing AtriPla to Eviplera on neurocognitive and emotional functioning) which was previously published (Hakkers et al 2019 ). In short, this randomised controlled trial included neurologically asymptomatic, stable (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Even in patients without clinically manifested cognitive complaints (cognitively asymptomatic patients), a negative effect of efavirenz on cognition has been shown (Robertson et al 2010). In the ESCAPE study, we found that discontinuing efavirenz led to an objective improvement in neurocognitive functioning in a group of asymptomatic people with HIV (Hakkers et al 2019). However, efavirenz remains a popular choice in antiretroviral therapy, mainly in resource-limited settings, mainly because is it part of Atripla, a single-tablet regime that is relatively cheap and has a convenient once a day dosage.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cART leads to reduced Myelin Basic Protein in the prefrontal cortex of HAND subjects 19 , and HIV+ subjects that withdraw from cART demonstrate improved cognition 20 . EFV (NNRTI) is linked neuropsychiatric effects (e.g., nightmares, dizziness, depression) and cognitive impairment [21][22][23] . Dolutegravir (DTG) is also linked to neuropsychiatric effects (sleep disturbance, depression) [24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%